Caracterização molecular de recursos genéticos de Cucurbita argyrosperma, Cucurbita ficifolia e Cucurbita pepo. - Priori, Daniela (2011)
Genetic resources conserved in genebanks have a great value in terms of conservation of rare types, when they are threatened by abandonment of farming or as a unique resource for plant breeding programs. Among the accessions conserved in genebanks important sources of genetic variability can be found for obtaining more productive genotypes tolerant to biotic and abiotic stresses and improved nutritional quality. To have success in that demand is necessary that the accessions contained in genebanks are characterized and evaluated in terms of both qualitative and quantitative characters. The characterization and evaluation of accessions conserved in genebanks must be priorities in the strategy for management of genetic resources, as they provide better knowledge of the germplasm available, is essential for use in breeding programs. In Brazil, there is little information on genetic resources of Cucurbits, especially as regards Cucurbita ficifolia, Cucurbita argyrosperma. Large number of Cucurbita landraces grown in the country could be better exploited as sources of genes for breeding programs, after genetic characterization. Much of the genetic diversity of different Cucurbita landraces grown in southern Brazil has been lost due to neglect of cultivation or its replacement by commercial hybrid varieties. This work was carried in order to contribute to general knowledge related to genetic resources of Cucurbita argyrosperma, Cucurbita ficifolia and Cucurbita pepo, and with specific objectives to assess the transferability of primers designed to C. pepo in C. argyrosperma and C. ficifolia and to evaluate the genetic variability within and among landraces of C. pepo grown in Rio Grande do Sul through analysis of microsatellite markers. Ten accessions of C. pepo, nine of C. argyrosperma and five of C. ficifolia belonging to the Active Germplasm Bank of Cucurbitaceae from Embrapa Temperate Agriculture were submitted to molecular characterization. The genetic distance between these accessions was determined. The transferability of SSR loci from C. pepo to C. argyrosperma and C. ficifolia was 85% and 80% respectively. The analysis of these 24 accessions with 35 loci generated a total of 105 SSR markers, ranging from one to four alleles per locus, of which 56 (53,33%) were polymorphic, showing that there is genetic diversity in the accessions analyzed. The presence and absence of markers allowed to find 100 loci, varying from one to five alleles per locus, with overall average of three alleles per marker analyzed. Among the 34 loci tested, 29 (85.2%) were polymorphic, showing that there is genetic variability among the accessions of C. pepo analyzed. Data evaluation was done by molecular analysis of molecular variance (AMOVA). It was observed that 54.60% of genetic variability is attributable to variation between accessions and 45.39% is attributed to differences within accessions. A comparative analysis was made between the ten accessions studied, analyzed two by two by AMOVA. From 45 comparisons between the ten accessions significant differences there were detected between 35 comparisons, with average of 57.10% of molecular variation attributed to differences between accessions. Genetic variation among counties where the accessions were collected was not significant, indicating that there is not population subdivision according to geographic region. Results indicate that the microsatellites were efficient for the characterization and molecular analysis of genetic divergence. These studies contributed to increase the knowledge related to these genetic resources. SSR primers developed for Cucurbita pepo can be used for molecular characterization of C. argyrosperma and C. ficifolia. Landraces of C. argyrosperma and C. ficifolia showed low genetic variation, while C. pepo shows great variability. The largest proportion of variability in C. pepo is distributed between accessions and not within accessions.